A Surveillance To Track Progress Toward Polio Eradication-Worldwide 2018-2023 : A Literature Review - Alifia Alifia Nabilla Salsabilla Zainudin (Journal of Diverse Medical Research : Medicosphere, 2025)
The near-complete eradication of polio is one of humanity's greatest achievements, yet surveillance remains critical to detect and interrupt poliovirus transmission. This study aims to analyze polio eradication surveillance programs in 28 priority countries over a five-year period (2018–2023). The primary method of poliovirus detection is acute flaccid paralysis (AFP) surveillance, confirmed by stool specimen testing, complemented by environmental surveillance (ES) through systematic sewage sampling to detect circulating polioviruses without relying on paralytic cases. Using a literature review with the PICO method, this study examined AFP quality data across 28 priority countries. The analysis reveals that while significant progress has been made, persistent challenges require urgent attention. Strengthening subnational surveillance is crucial to prevent undetected cases. Countries with low stool adequacy rates must improve sample collection and transportation, particularly in remote and conflict-affected areas. Given its success in early virus detection, environmental surveillance should be further expanded, especially in high-risk regions with weak AFP surveillance. Achieving global polio eradication demands continued investment, robust surveillance systems, and targeted interventions in vulnerable areas.